Novel air leak test and step-by-step strategy for preventing the air leak in lung surgery - Yang, Hee Chul; Chang, Hye Young (Journal of Thoracic Disease, 2019)
Receiving sincere comments from experts in the field on technology that shows new direction and possibility can be a great foundation for further development. Three (1-3) editorials expressed their curiosities and concerns for our study (4) as follows.